2022
DOI: 10.48550/arxiv.2208.08449
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recent Developments in Fractional Chern Insulators

Abstract: Fractional Chern insulators (FCIs) are lattice generalizations of the conventional fractional quantum Hall effect (FQHE) in two-dimensional (2D) electron gases. They typically arise in a 2D lattice without time-reversal symmetry when a nearly flat Bloch band with nonzero Chern number is partially occupied by strongly interacting particles. Band topology and interactions endow FCIs exotic topological orders which are characterized by the precisely quantized Hall conductance, robust ground-state degeneracy on hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 193 publications
(349 reference statements)
0
3
0
Order By: Relevance
“…Recently, the bosonic 1∕2-Laughlin state, [26] a hallmark of the FQHE, has DOI: 10.1002/qute.202300356 been demonstrated in photonic [27] and ultracold atomic systems in the few-body regime. [28] Another family of systems that exhibit FQHE-like behavior are fractional Chern insulators (FCIs), [29][30][31] which are lattice analogues of FQH phase with [32][33][34][35][36][37] or without LLs. [38][39][40][41][42][43][44][45][46] The latter are also called fractional quantum anomalous Hall (FQAH) insulator, and can be achieved by replacing fractionally filled LLs by fractionally filled topological flat bands that have zero net flux.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the bosonic 1∕2-Laughlin state, [26] a hallmark of the FQHE, has DOI: 10.1002/qute.202300356 been demonstrated in photonic [27] and ultracold atomic systems in the few-body regime. [28] Another family of systems that exhibit FQHE-like behavior are fractional Chern insulators (FCIs), [29][30][31] which are lattice analogues of FQH phase with [32][33][34][35][36][37] or without LLs. [38][39][40][41][42][43][44][45][46] The latter are also called fractional quantum anomalous Hall (FQAH) insulator, and can be achieved by replacing fractionally filled LLs by fractionally filled topological flat bands that have zero net flux.…”
Section: Introductionmentioning
confidence: 99%
“…TFBs with non-zero Chern number play the similar role as the Landau levels, and they can effectively quench the kinetic energy and enhance interaction. When interacting particles fill into TFB models, several numerical and analytical studies have systematically revealed the existence of fractional CI (FCI) states [14,17,18,[26][27][28][29][30][31][32][33][34][35]. Therefore, finding TFB models becomes meaningful for the realization of FCIs.…”
Section: Introductionmentioning
confidence: 99%
“…Exploring and discovering exotic phases of interacting matter such as fractional Chern and topological Mott insulators remains a primary objective in this field [5,6]. However, due to the complexity of interacting manybody problems, a bottom-up approach examining the exactly solvable two-body problem in a multiband Hubbard model can sometimes be useful [7].…”
Section: Introductionmentioning
confidence: 99%